The Effect of Metalinguistic Written Corrective Feedback on English Writing Competency of the Eighth Grade Students of SMPN 1 Abiansemal in Academic Year 2015/2016 - S A Gasella; Dewa Putu Ramendra; I Nyoman Pasek Hadisaputra (Lingua Scientia, 2016)
The present study aimed at investigating whether or not there was a significant difference in writing competency between the eighth grade junior high school students who received metalinguistic WCF and those who did not receive any feedback. This experimental study took the eighth grade students in SMPN 1 Abiansemal as the population and VIIIB and VIIIF respectively as the control and experimental group through cluster random sampling. The design of the study was pretest-posttest control group design. The data were the students’ pretest and posttest that were analyzed descriptively and inferentially. ANCOVA test was used in analyzing the data and to test the hypothesis. The result of the analysis using ANCOVA in SPSS 17.0 showed that the significance value of the group was 0.024 which was lower than the significance level 0.05. It means that the null hypothesis was rejected. It was concluded that there was a significant difference between students who received metalinguistic WCF and those who did not receive any feedback.